Surgical Management for Resistant Gestational Throphoblastic Neoplasia: Yogyakarta Experience - Greta S Gulo; Nirwan Darmawan; Bob Irsan; Wisnu Prabowo; Ardhanu Kusumanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Gestational trophoblastic neoplasia (GTN) is a highly responsive to chemotherapy, but sometimes can be resistant, or relapse and require salvage chemotherapy with or without surgery. We use descriptive studies with case series to determine prognosis patient GTN with chemotherapy resistant manage with surgical procedure in Sardjito Hospital, Yogyakarta. GTN-resistant chemotherapy patients that undergoing hysterectomy showed significant decreases in hCG levels. Hysterectomy also help us to stop vaginal bleeding. However, complications from continuous bleeding can worsen patient condition. The decision to take a hysterectomy action varies depending on the patient's condition. At the Sardjito hospital, the patient was diagnosed with the fastest hysterectomy within the first 12 hours of treatment due to continuous bleeding, and shortly after 4 years of treatment with 5 different types of chemotherapy.